How to avoid life-threatening complications following head and neck space infections: an algorithm-based approach to apply during times of emergency. When and why to hospitalise a neck infection patient. Issue 1 (6th November 2017) - Gallo, O; Mannelli, G; Lazio, M S; Santoro, R
Abstract: Background: Head and neck space infections present with a potential mortality rate of 40–50 per cent. This paper proposes an algorithm-based management of head and neck space infection to prevent life-threatening events. Methods: A total of 225 patients with head and neck space infection were prospectively analysed at our institution. An experimental scoring system determined the level of clinical risk for the development of major complications. Accordingly, patients were classified into three risk groups: low-, intermediate- and high-risk. Results: Only intermediate- and high-risk patients were hospitalised. Intermediate-risk patients received intravenous medical therapy with daily re-evaluation; 18 of them required delayed surgery. Of the high-risk patients, three required immediate surgical treatment and five received delayed surgery, while in five cases medical therapy was the only treatment received. Low-risk patients were treated in an out-patient setting. Conclusion: The algorithm-based management of head and neck space infection was successful in enabling the avoidance of lethal complications onset.